TOTAL LIGNIN CONTENT AND AGROMORPHOLOGICAL CHARACTER DIVERSITIES OF 30 INDONESIAN RICE (Oryza sativa L.) ACCESSIONS - Nugroho, Satya (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2022)
Lignin is one of lignocellulosic components in vascular plants, essential in plant mechanical properties, water transport, and defense against pathogens. Furthemore, lignin has been applied in various industry. This study aimed to explore variation of lignin content and its-related morphological traits of Indonesian rice accessions, providing beneficial information for breeding approaches to improve utilization characteristics of grass biomass. Therefore, the total lignin contents of thirty Indonesian rice accessions using Thioglycolic Acid Lignin (TGAL) method and their correlation to seven agromorphological characters using Pearson correlation analysis were investigated. Variation of lignin content ranged from 8.38 to 20.75% (of cell wal residue, CWR), and the average value was 13.55%. Correlation analysis showed that lignin total positively correlated with plant height, stem length, panicle length, stem diameter, total fresh weight, and panicle weight per tiller. On the other hand, the number of tillers had a significantly negative correlation to lignin contents.